RANCANGAN SISTEM INFORMASI KEUANGAN PADA QDOORSMEER & COFFEE - Andriani, Kiki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The purpose of this study is to determine and design a Financial Information System Design at Qdoorsmeer & Coffee using a web-based programming language. In making this model the researcher compiles using a flowchart and is used for a graphical depiction of the steps and sequence of procedures of a program. While in the prototype development process using the waterfall method. Based on the results of the study, the authors can draw a conclusion which includes the following; 1) The use of the Financial Information System at QDoorsmeer & Coffee is expected to help create accurate and effective transaction information data, and 2) The information system provides convenience for QDoorsmeer & Coffee because it speeds up information in general and reduces errors.